'Our students do not get that equal chance': teachers' perspectives of meritocracy. Issue 2 (4th March 2021) - Ho, Li-Ching
ABSTRACT: This study explores how Singapore social studies, geography and history teachers make meaning of the concept of meritocracy and its role in the education system. The findings indicate the participants simultaneously adopted and challenged the meritocratic values and beliefs promoted by the Singapore state. The teachers strongly believed that the principle of meritocracy helped promote educational and social equality, but they were also deeply concerned about the limitations of meritocracy and the impact of structural and institutional inequalities on educational equality. Even though most participants were able to identify and critique structural inequities and explain how this could affect students' academic achievement, their awareness of the limitations of the meritocratic system did not undermine their belief in the system of meritocracy and they could not envisage alternative systems for determining educational access and equality.